Cultural Variations in Evaluation of Creative Work: A Comparison of Russian and Emirati Samples - Kharkhurin, Anatoliy V.; Yagolkovskiy, Sergey R. (Frontiers in Psychology, 2021)
The study investigates how cultural variations influence evaluation of creative work. Russian and Emirati undergraduate college students were asked to judge alien creature drawings produced by their countrymates in previous studies’ structured imagination test. We found cultural differences in creativity judgment. Emirati participants’ judgments were significantly lower than Russian participants’ judgments. We also found that Russians judged their compatriots significantly higher than the Emirati judged their compatriots. Russians also judged foreigners significantly lower than the Emirati judged foreigners. These findings were speculatively placed in the context of the cultural differences in the implicit theory of creativity.